(untitled) (Indian Journal of Animal Production and Management, 2015)
The experiment was conducted to know the effect of stocking density on growth and carcass characteristics of Japanese quail in floor rearing. Four hundred thirty two no. of quail chicks (variety-CARI Brown) were procured from Central Poultry Development Organization, Bhubaneswar and were brooded up to 14 days. Then these 14 day old chicks were divided in to 4 groups consisting of 108 no. of chicks each. Each group were divided into three Effect of stocking density on Japanese quailreplicates, having 36 no. of chicks. Study was undertaken during the growing period (15-35 days) with the following floor space provisions in the four groups, G1–150 cm2/chick, G2–200 cm2/chick, G3–250 cm2/chick, G4–300 cm2/chick. In 3rd week, G3 showed the highest gain (52.58 ± 0.42 g) followed by G4 (50.37 ± 0.57 g), G2 (48.31 ± 0.70 g) and G1 (39.68 ± 0.48 g).Group G3 showed significantly (Pd”0.05) higher gain than G1 or G2, while it did not differ significantly (Pe”0.05) from G4. Group G4 showed a significantly (Pd”0.05) higher gain than either G2 or G1. In 4th week, G3 showed the highest gain (82.97 ± 0.92 g) followed by G4 (79.46 ± 0.81 g), G2 (76.81 ± 1.15 g) and G1 (66.71 ± 2.18 g). Groups G2, G3 and G4 did not differ significantly (Pe”0.05) between them, while each of these three groups had higher gains (Pd”0.05) than G1. In case of FCR the groups with 200, 250 and 300 cm2 per bird stocking densities did not differ significantly (P>0.05), while each of these groups showed significantly (P < 0.05) lower FCR than the group with 150 cm2 per bird floor space. For dressing yield, group G3 had significantly (Pd”0.05) higher yield than G1. It was concluded that provision of an optimal floor space 250 cm2 per bird resulted in higher body weight, gain in body weight, feed efficiency, dressed and eviscerated yield.